Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging - Hoskere, Anila A.; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S-n, specifically senses intracellular hydrogen polysulfides (H2Sn, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2Sn by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).